Enhanced mass transport in liquid-saturated porous media due to surface shear - David J. Richardson (1999)
The principal aim of this work was the development of a novel conductivity probe for measuring solids concentrations in slurries. The relevance of the thesis to this probe is that it requires rapid transport of aqueous electrolyte through a porous disc to an internal conductivity cell. [Continues.]